2019
DOI: 10.1038/s41419-019-1801-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of venetoclax activity in precursor B-ALL by functional assessment of apoptosis signaling

Abstract: Deregulated cell death pathways contribute to leukemogenesis and treatment failure in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Intrinsic apoptosis signaling is regulated by different proapoptotic and antiapoptotic molecules: proapoptotic BCL-2 homology domain 3 (BH3) proteins activate prodeath molecules leading to cellular death, while antiapoptotic molecules including B-cell lymphoma 2 (BCL-2) prevent activation of prodeath proteins and counter-regulate apoptosis induction. Inhibition of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 53 publications
6
40
0
Order By: Relevance
“…Furthermore, the inability of Trametinib to potently sensitize GB cells for cell death, might be due to its inability to break the intrinsically high resistance to apoptosis exhibited by GB cells. ERK is described to affect cell death via modulation of the Bcl-2 family 60 , which only plays a relative minor role in GB [61][62][63][64] compared to, for example, in leukaemia, where blocking Bcl-2 can be sufficient to induce apoptosis 65 . However, ERK is also involved in immune-resistance/immune-escape of cancer cells 60 , a potential interesting therapeutic avenue not addressed by this work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inability of Trametinib to potently sensitize GB cells for cell death, might be due to its inability to break the intrinsically high resistance to apoptosis exhibited by GB cells. ERK is described to affect cell death via modulation of the Bcl-2 family 60 , which only plays a relative minor role in GB [61][62][63][64] compared to, for example, in leukaemia, where blocking Bcl-2 can be sufficient to induce apoptosis 65 . However, ERK is also involved in immune-resistance/immune-escape of cancer cells 60 , a potential interesting therapeutic avenue not addressed by this work.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated cell death pathways contribute to treatment failure in ALL. 131 Preclinical studies have identified activities of venetoclax against high-risk leukemias such as ETP ALL, KMT2A-rearranged ALL, TCF3-HLF-positive ALL, and hypodiploid ALL (Table 2). 132,133 Proteasome and mTOR inhibitors have shown efficacy in relapsed ALL.…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%
“…Copy number alterations of genes and chromosomal arms were assessed by Multiplex Ligation‐dependent Probe Amplification (MLPA) with SALSA MLPA P335‐B2 ALL‐IKZF1 probemix and SALSA MLPA P181‐B1 Centromere probemix (MRX‐Holland, The Netherlands), according to manufacturer's instructions. The presence of fusion transcripts was analyzed by RT‐PCR as previously described …”
Section: Methodsmentioning
confidence: 99%
“…The presence of fusion transcripts was analyzed by RT-PCR as previously described. 30 Expression of DIPK1C, MTX2, TSPAN7 and TNFRSF1A as biomarker of SM sensitivity Expression of DIPK1C, MTX2, TSPAN7 and TNFRSF1A was assessed by qRT-PCR in BCP-ALL cell lines and xenografts.…”
Section: Multiplex Ligation-dependent Probe Amplificationmentioning
confidence: 99%